Analysis Of Occupational Health And Safety (Ohs) Risk In The 50 Kg Tube Welding Assembly Process At Pt Pindad Using The Hirarc (Hazard Identification Risk Assessment And Risk Control) Method - Firstian Rizky, Raihan Zhafranu; Widaningrum, Sri; Salma, Sheila Amalia (eProceedings of Engineering, 2024)
PT Pindad is a company engaged in themanufacturing industry, which involves the production processas well as a lot of critical operational work, this raises concernsregarding the continuity of the activity process, where it ispossible to cause work accidents ranging from minor to major,which causes serious injuries and even death. The purpose ofthis study is to identify the hazards and risks that occur and alsoprovide suggestions for improving the occupational safety andhealth management system at PT Pindad. An analysis has beencarried out based on the problems encountered using a fishbonediagram. Therefore, the HIRARC method was chosen as asupport for solving existing problems at PT Pindad. Thisresearch uses a qualitative descriptive research method.Identification was carried out on 23 activities, and after carryingout a risk assessment based on HIRARC, 3 risks were found andthe causes of events that gave rise to high risk factors wereidentified, namely, welding process activities, operator orworker position activities in welding, and material refiningactivities. The proposed design of OHS risk control is given byreferring to five risk control hierarchies: elimination,substitution, engineering, administration, and personalprotective equipment. Keywords— HIRARC, OHS, Work Accident